Pendidikan Jasmani sebagai Sarana Pengembangan Motorik dan Mental Peserta Didik: Tinjauan Literatur - Zulfan Heri; Putra Arima; Febrian Naibaho; Rafif Ahmad Yulfiza; Michael Risky hasiolan Sianipar (Universitas Negeri Medan, 2026)
Physical education is an important part of the educational process that plays a role in supporting the motor and mental development of students. This article aims to review various literature discussing the contribution of physical education to motor development as well as the mental condition of students in the school environment. The method used is a literature study by examining various scientific articles, books, and relevant academic sources in recent years. The results of the review show that physical education has a positive impact on the improvement of basic motor skills, movement coordination, balance, agility, and students' physical fitness. In addition, participation in physical education activities also contributes to mental development, such as increased self-confidence, discipline, learning motivation, teamwork skills, and better emotion management. These findings indicate that physical education not only functions as a means physical development facilities, but also as a medium for forming students' character and mental health. Therefore, the implementation of physical education needs to be continuously optimized in the educational process to support students' overall development